Nigella sativa and Cancer: A Review Focusing on Breast Cancer, Inhibition of Metastasis and Enhancement of Natural Killer Cell Cytotoxicity - Korak, Tuğcan; Ergül, Emel; Sazci, Ali (Current Pharmaceutical Biotechnology, 2020)
Background: In the last decade, there have been accumulating data that the use of medicinal plants could bring additional benefits to the supportive treatment of various diseases. Nigella sativa (N. sativa, family Ranunculaceae) is one of these plants that has attracted considerable interest. The extracts and seeds of N. sativa and its active component thymoquinone have been studied extensively and the results suggest that N. sativa might carry some therapeutic potential for many diseases, including cancer. Methods: The selection criteria for references were applied through Pubmed with “N. sativa and cancer”, “N. sativa and breast cancer”, “N. sativa and metastasis”, “N. sativa and cytotoxicity of natural killer cells”. The pathway analysis was performed using the PANTHER tool by using five randomly selected N. sativa affected genes (Cyclin D1, P53, p21 protein (Cdc42/Rac) activated kinase 1 (PAK1), B-cell lymphoma 2 (Bcl-2) and vascular endothelial growth factor (VEGF)) in order to elucidate further potentially affected signaling pathways. Results: The aim of this review was to summarize studies regarding the effects of N. sativa in cancer generally, with a focus on breast cancer, its anti-metastatic effects, and how N. sativa modulates the cytotoxicity of Natural Killer cells that play a crucial role in tumor surveillance. Conclusion: In summary, the data suggest that N. sativa might be used for its anti-cancer and antimetastatic properties and as an immune system activator against cancer.
Keywords: natural killer cells